Pengaruh Reward, Punishment dan Psikologis terhadap Kecurangan Akademik Mahasiswa di Alhimni Education Center Mojokerto - Cici Wulan Purnama; Hari Setiono; Muhammad Bahril Ilmiddaviq (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The purpose of this study was to examine the effect of reward, punishment and psychology on academic cheating. This type of research is quantitative with a population of 39 students at Alhimni Education Center and a sample of 31 results from the purposive sampling method. The data used are primary data through questionnaires and measured by a Likert scale. The data analysis technique uses descriptive statistics through the SmartPLS testing tool with outer model and inner model measuring instruments. The results of the study showed that punishment had a negative and significant effect. While reward had a negative effect and psychology had a positive effect but both were not significant.